Sorption behaviour of perfluoroalkyl substances in soils - Milinovic, Jelena; Lacorte, Silvia; Vidal, Miquel; Rigol, Anna (The Science of the total environment, 2015)
The sorption behaviour of three perfluoroalkyl substances (PFASs), perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA) and perfluorobutane sulfonic acid (PFBS), was studied in six soils with contrasting characteristics, especially in the organic carbon content. Sorption isotherms were obtained by equilibrating the soil samples with 0.01molL−1 CaCl2 solutions spiked with increasing concentrations of the target PFAS. The sorption reversibility of PFASs was also tested for some of the samples. Liquid chromatography coupled to tandem mass spectrometry was used to quantify the target PFASs in the solutions. Both the Freundlich and linear models were appropriate to describe the sorption behaviour of PFASs in soils, and enabled us to derive solid–liquid distribution coefficients (Kd) for each compound in each soil. Kd values increased from 19 to 295mLg−1 for PFOS, from 2.2 to 38mLg−1 for PFOA and from 0.4 to 6.8mLg−1 for PFBS, and were positively correlated with the organic carbon content of the soil. KOC values obtained from the correlations were 710, 96 and 17mLg−1 for PFOS, PFOA and PFBS, respectively. Whereas Kd values decreased in the sequence PFOS>PFOA>PFBS, desorption yields were lower than 13% for PFOS, from 24 to 58% for PFOA, and from 32 to 60% for PFBS. This shows that the physicochemical characteristics of PFASs, basically their hydrophobicity, controlled their sorption behaviour in soils, with PFOS being the most irreversibly sorbed PFAS. •Sorption isotherms of PFOS, PFOA and PFBS in soils are linear.•Sorption affinity of PFASs increases with the hydrophobicity of the compound.•Sorption reversibility decreases when the hydrophobicity of the PFAS increases.•Sorption Kd correlates to the soil organic matter content.•KOC values are obtained from the Kd-organic matter correlation.